1995
DOI: 10.1159/000139350
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Function of the Vascular Endothelium in Portal Hypertensive Rats

Abstract: There were no differences between mesenteric arteries from sham or 14-day portal hypertensive (PH) rats in the potency of or maximum endothelium-dependent relaxations (EDR) to acetylcholine. There were no differences between sham-operated and PH rats in the effects of the combination of the nitric oxide synthase inhibitor NG-monomethyl-L-arginine (100 µmol/l) and methylene blue (10 µmol/l) in causing a significant reduction in the EDR to acetylcholine. The degree of portal-systemic shunting, as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…The increased contractile responsiveness of the aorta found in this study, and of the mesenteric artery in our previous study [12,13], contrasts with reports of decreased responsiveness of the in situ mesenteric vascular bed of pre-hepatic portal hypertensive rats or cirrhotic rats to vasoconstrictors such as noradrenaline, endothelin-1 and angiotensin II [7][8][9]17,18]. Pressor responses to angiotensin II also decreased in bile duct-ligated dogs [19].…”
Section: Strain Days Agonistcontrasting
confidence: 99%
See 1 more Smart Citation
“…The increased contractile responsiveness of the aorta found in this study, and of the mesenteric artery in our previous study [12,13], contrasts with reports of decreased responsiveness of the in situ mesenteric vascular bed of pre-hepatic portal hypertensive rats or cirrhotic rats to vasoconstrictors such as noradrenaline, endothelin-1 and angiotensin II [7][8][9]17,18]. Pressor responses to angiotensin II also decreased in bile duct-ligated dogs [19].…”
Section: Strain Days Agonistcontrasting
confidence: 99%
“…We have previously reported that the maximum contractile responses to noradrenaline, KCl and the thromboxane mimetic U46199 are significantly increased in mesenteric arteries from portal hypertensive Wistar rats compared with sham-operated animals [12,13]. In comparison, many of the above mentioned studies of portal hypertension employed the Sprague-Dawley rat and examined aortic rings.…”
Section: Introductionmentioning
confidence: 99%
“…Seven days after portal vein ligation, shunting was 66.5±14.3% ( n = 3). This result correlated well with values for degree of shunting obtained 7 days post ligation by Cawley et al (1995b).…”
Section: Resultssupporting
confidence: 85%
“…In this study we confirmed that our animals were portal hypertensive by examining, with the radioactive microsphere techique, the degree of shunting. Porto‐systemic shunting is effectively nil up to 3 days post portal vein ligation, but is near maximum 7 days post ligation (Cawley et al , 1995b). At seven days post ligation we showed that there was 66.5±14.3% porto‐systemic shunting, similar to values obtained by Cawley et al (1995b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation